KEHIDUPAN SOSIAL EKONOMI PEKERJA PEREMPUAN DI PABRIK PENGOLAHAN IKAN SETELAH PEMBERLAKUAN REGULASI MENTERI KELAUTAN TENTANG ILEGAL FISHING TAHUN 2014 (Study kasus di kota Bitung) - Pratiknjo, Maria Heny (Universitas Sam Ratulangi, 2018)
Over time, the level of modernization and information that is increasingly global, the success of the women's emancipation movement and awareness about gender roles then predicted ahead the public sector will be much loved and absorb labor women. In the exercise we can see that the dual role of women resulted in a shift in values within the family structure changes in functional form in the allocation of time and activities for families, household affairs, social work economy, self development and utilization of free time. Awareness of the economic aspect of the right to life as well as the responsibility for fulfilling personal needs and family have pushed humans to strive to enter into the world of work. Keterpanggilan to work outside the home in the public sector with the aim of earning. The town of Bitung is a hub of business development of fisheries in North Sulawesi province in terms of the infra structure is very supportive of the area became a producer of fishery products for the domestic market and abroad (Department of agriculture and fisheries 2014 year in North Sulawesi). As for the number of factories in the town of Bitung fish manager until the year 2014 totaled 53 factory, which consists of a number of qualifying effort with workers until 2014 thn amounted to 12,848 March 2017 and hoses down drastically and left over 2000 workers. (Department of Fisheries and marine Prov. Flammable). Needs to be taken anticipatory measures for the empowerment of women workers get around given many a domino effect that will occur, among others, an increase in crime. This study uses qualitative methods, in-depth interviews and observations through using triangulation techniques in data collection.Â Keywords: women, industrial workers, regulation